2018
DOI: 10.1016/j.biocontrol.2018.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Perennial fallow strips support biological pest control in spring cereal in Northern Europe

Abstract: Fallow strips are promoted through agri-climate-environment schemes to enhance farmland biodiversity, but their effects on biodiversity-mediated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 70 publications
3
23
0
Order By: Relevance
“…, Toivonen et al. ). Conversely, some researchers worry that wildflower plantings will augment pest species that can invade crops (Baggen and Gurr , Frank , Marshall and Moonen ).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…, Toivonen et al. ). Conversely, some researchers worry that wildflower plantings will augment pest species that can invade crops (Baggen and Gurr , Frank , Marshall and Moonen ).…”
Section: Introductionmentioning
confidence: 98%
“…However, overall arthropod abundance and diversity within wildflower plantings is poorly understood and has not been thoroughly explored (Toivonen et al. ), especially in key agricultural areas like Florida (USA). In this study, we examined eight wildflower plots paired with fallow plots to document pollinating insect abundance and richness.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that sowing WFS adjacent to crops enhances biological control of insect pests due to an increased abundance of natural enemies (Tschumi et al 2016;Hatt et al 2017a;Toivonen et al 2018). Indeed, generalist predators such as hoverflies (Diptera: Syrphidae), ladybeetles (Coleoptera: Coccinellidae) and lacewings (Neuroptera:…”
Section: Introductionmentioning
confidence: 99%